The Function Of Public Accountant Company In Pressuring Audit Report Delays For Firms That Are Going Public In Indonesia: Panel Analysis - M. Anas; Faisol Faisol; Puji Astuti (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: The purpose of this essay is to look into how Public Accounting Company (PAC) link important factors like Audit Tenure, Company Size, and Financial Distress with Audit Report Lag. We delve further to comprehend how PAC mediates this link and whether its impact is considerable in shortening the delay for filing audit reports. Method/approach: The population of this study consists of operating in the mining industry companies registered on the Indonesia Stock Exchange from 2015 to 2022. The sampling method used is purposive sampling method. The samples were obtained by 19 manufacturing companies. There were 152 observations made over 8 years. The data analysis used was panel regression analysis which was moderated by using the random effect model approach. Findings: The analysis's findings indicate that Public Accounting Company (PAC) is significantly involved in mediating the association between financial distress and audit report lag, but that PAC is not significantly involved in mediating the relationship between business size and audit tenure and audit report lag. Implications: According to the findings, it is essential for a Public Accounting Company (PAC) to be involved in the audit process when a company is in financial trouble. In order to keep the audit report lag under control during financially difficult times, PACs appear to be quite important. This emphasises how crucial skilled auditors are in identifying and resolving any financial problems that can develop in struggling businesses. Originality/value: This publication presents originality in uncovering the innovative role of Public Accounting Company (PAC) as mediators that link the Audit Tenure, Company Size and Financial Distress variables with Audit Report Lag. This research explores how the complex interactions between these variables impact delays in audit report submission. The findings highlight that PAC is not only the implementing audit entity, but also plays an important role in controlling the timing of preparation and submission of audit reports. These findings provide new insights into the dynamics of auditing and management decisions in the context of corporate financial uncertainty